Scale Evaluation of the Trans Batam Passenger Information System Application (SIP TB) Using the System Usability Scale Method - Dira Septiani; Adhitomo Wirawan; Fatma Saqdiah; Aulia Fajrin (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to evaluate the Usability of the Trans Batam Passenger Information System (SIP TB) application using the System Usability Scale (SUS). The study involves 200 respondents who use the SIP TB application in Batam City. The quantitative method used includes questionnaire distribution and SUS scoring analysis. The results show that the average SUS score is 76, placing the application in the "Good" category and falling within the "Acceptable (High)" range. The Grade Scale also falls under category C. These results indicate that the application is generally usable, although there is room for improvement, particularly in user interface design and cross-platform availability.